Modeling and Simulation for the Coordinated Development of Sports -Economy Complex System Based on Complex System Theory - Ruixue Zhang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The regional development of the sports industry and its role in the economy could be potentially facilitated by more research into the sports – economy complex system (SECS). However, the existing studies on SECS overlook the differences between the subsystems, failing to systematically analyze the features of each individual subsystem or the complex system in different phases. Thus, the basic purpose of this research is to solve the major and urgent problems regarding the regional complex system in order to advance the research on SECS. Based on the theory of complex systems, this paper mainly studies the coordinated regional development between sports and economy and constructs a model for simulation and verification. Specifically, the authors examine the relationship between sports development and regional economic growth, modeling the coordination of SECS in the course of development, and setting up an evaluation index system (EIS) for the coordinated development of SECS. For this purpose, the experimental research design is used in this study as the research methodology. On this basis, the accelerated genetic algorithm (AGA) is introduced to evaluate the coordinated development of that system. The proposed model is proved valid through experiments.